2021
DOI: 10.14366/usg.20157
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced voiding urosonography for the diagnosis of vesicoureteral reflux and intrarenal reflux: a comparison of diagnostic performance with fluoroscopic voiding cystourethrography

Abstract: Contrast-enhanced voiding urosonography for the diagnosis of vesicoureteral reflux and intrarenal reflux: Comparison of diagnostic performance with fluoroscopic voiding cystourethrography

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 23 publications
5
13
0
1
Order By: Relevance
“…Out of all the detected VURs, the percentage of detected IRRs in this study was 47.5%. If we exclude the results of Cvitkovic Roic et al who reported 12% IRR, other studies also showed a higher incidence of IRR on ceVUS, which is a much higher incidence than in patients examined by VCUG, which has been reported to be 1–11% ( 17 , 19 , 20 , 22 , 25 , 26 ).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Out of all the detected VURs, the percentage of detected IRRs in this study was 47.5%. If we exclude the results of Cvitkovic Roic et al who reported 12% IRR, other studies also showed a higher incidence of IRR on ceVUS, which is a much higher incidence than in patients examined by VCUG, which has been reported to be 1–11% ( 17 , 19 , 20 , 22 , 25 , 26 ).…”
Section: Discussionmentioning
confidence: 75%
“…Since IRR was assigned as a potential place of parenchymal damage in the previous studies ( 17 , 22 , 23 , 29 , 30 ), we expect more parenchymal changes at the places of IRR in this study. Moreover, since a higher number of IRRs can be detected by ceVUS than by VCUG ( 19 , 26 ), we expect some other signs of parenchymal damage, not only scars, diagnosed by DMSA scan in renal regions affected by IRR in patients diagnosed by ceVUS.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Likewise, in the analysis of DMSA scans, multiple IRRs in a single pole were evaluated as a single lesion, and the largest IRR was selected among multiple lesions. We classified IRR into three types according to its extent, as follows [ 10 ]: type 1 IRR, mild IRR (confined to a single medullary pyramid, which was seen as a string of tiny bubbles refluxed into the medulla with CeVUS); type 2 IRR, moderate IRR (involving several tiny bubbles refluxed into less than half of the renal parenchyma); type 3 IRR, extensive IRR (involving more than half of the renal parenchyma) ( Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…From this perspective, contrast-enhanced voiding ultrasonography (CeVUS), an ionizing radiation-free alternative to fluoroscopic VCUG, is an emerging A c c e p t e d A r t i c l e modality for the diagnosis of VUR. In addition, there have been some reports suggesting that CeVUS could depict IRR better than conventional VCUG [8][9][10][11]. Therefore, we assume that CeVUS, which shows high sensitivity in diagnosis of IRR, would be highly correlated with the sites of photon defects on acute DMSA renal scans.…”
Section: Introductionmentioning
confidence: 96%